Social impact measurement as a tool of governance and accountability for waqf organisations - Zain, Nor Syahirah; Hassan, Rusni; Syed Azman, Syed Marwan Mujahid (Penerbit KUIS, 2023)
This paper explores the role of Social Impact Measurement (SIM) as a tool for governance and accountability in waqf organisations, focusing on Malaysia. It investigates the application of SIM in four waqf organisations in Malaysia and aims to contribute to the understanding of its potential benefits and application. The study undertakes a critical review of the literature on governance practices within waqf organisations and examines how SIM could potentially enhance governance and accountability. Additionally, semi-structured interviews are conducted with four waqf institutions in Malaysia to gain insights into their SIM practices. The findings of the study show a positive correlation between effective SIM practice, good governance, and accountability. The interviews reveal the understanding of SIM, its implementation and challenges faced among waqf administrators in Malaysia. This study has limitation since only four waqf organisations were interviewed. However, this is a fair representation of each waqf category in Malaysia. Future research may expand the coverage to include more organisations in and outside of Malaysia. Further studies can also be designed to address the challenges identified and propose a comprehensive SIM framework tailored specifically for waqf organisations. In terms of practical implication, the findings of the study have significant implications for the government, waqf administrators, regulators, policymakers, and stakeholders interested in advancing SIM practices in waqf organisations. Recommendations are made to drive the implementation of SIM among waqf players, including increasing awareness of SIM and providing support, guidelines, and motivations to waqf organisations. This study also introduces and advocates for the adoption of SIM practices in waqf in Malaysia, highlighting their significance. Promoting good governance and accountability via SIM can enhance the multifaceted roles of waqf organisations in society.